Desenvolvimento de um ressoador retangular de fenda com múltiplas camadas de substrato e com utilização de material PBG para sistema de comunicação sem fio - Andrade, Humberto Dionísio de (2013)
In the globalized world modern telecommunications have assumed key role within the company, causing a large increase in demand for the wireless technology of communication, which has been happening in recent years have greatly increased the number of applications using this technology. Due to this demand, new materials are developed to enable new control mechanisms and propagation of electromagnetic waves. The research to develop new technologies for wireless communication presents a multidisciplinary study that covers from the new geometries for passive antennas, active up to the development of materials for devices that improve the performance at the frequency range of operation. Recently, planar antennas have attracted interest due to their characteristics and advantages when compared with other types of antennas. In the area of mobile communications the need for antennas of this type has become increasingly used, due to intensive development, which needs to operate in multifrequency antennas and broadband. The microstrip antennas have narrow bandwidth due to the dielectric losses generated by irradiation. Another limitation is the degradation of the radiation pattern due to the generation of surface waves in the substrate. Some techniques have been developed to minimize this limitation of bandwidth, such as the study of type materials PBG - Photonic Band Gap, to form the dielectric material. This work has as main objective the development project of a slot resonator with multiple layers and use the type PBG substrate, which carried out the optimization from the numerical analysis and then designed the device initially proposed for the band electromagnetic spectrum between 3-9 GHz, which basically includes the band S to X. Was used as the dielectric material RT/Duroid 5870 and RT/Duroid 6010.LM where both are laminated ceramic-filled PTFE dielectric constants 2.33 and 10.2, respectively. Through an experimental investigation was conducted an analysis of the simulated versus measured by observing the behavior of the radiation characteristics from the height variation of the dielectric multilayer substrates. We also used the LTT method resonators structures rectangular slot with multiple layers of material photonic PBG in order to obtain the resonance frequency and the entire theory involving the electromagnetic parameters of the structure under consideration. xviii The analysis developed in this work was performed using the method LTT - Transverse Transmission Line, in the field of Fourier transform that uses a component propagating in the y direction (transverse to the real direction of propagation z), thus treating the general equations of the fields electric and magnetic and function. The PBG theory is applied to obtain the relative permittivity of the polarizations for the sep photonic composite substrates material. The results are obtained with the commercial software Ansoft HFSS, used for accurate analysis of the electromagnetic behavior of the planar device under study through the Finite Element Method (FEM). Numerical computational results are presented in graphical form in two and three dimensions, playing in the parameters of return loss, frequency of radiation and radiation diagram, radiation efficiency and surface current for the device under study, and have as substrates, photonic materials and had been simulated in an appropriate computational tool. With respect to the planar device design study are presented in the simulated and measured results that show good agreement with measurements made. These results are mainly in the identification of resonance modes and determining the characteristics of the designed device, such as resonant frequency, return loss and radiation pattern